Design And Implementation Of A Rotary Automated Parking System Using PLC Based Control System - Muhammad Asyraf Bin Mahmood (2023)
Simultaneously with the growing population of human in cities, the need of automobiles is also keep increasing from past few decades. The use of the traditional parking system is causing many problems such as the consumption of space, waste of productivity hour, high fuel usage and more.